Analisis Relevansi Nilai PSAK No. 30 (Revisi 2007) tentang Sewa, Dinilai Berdasarkan Reaksi Pasar Modal - Sari, Dewi Kartika (UI Scholars Hub, 2013)
As one of the IFRS convergence program, DSAK-IAI has made several revisions of financial accounting standards, one of which is PSAK No. 30 (Revisi 2007) about Leases. These financial accounting standards have become effective since January 1, 2008. But until now still a few companies that apply this standard. This is probably because the company did not know the financialbenefitofthe application ofthisstandard. Thereforethis studywas conducted to determinethe value relevance of PSAK No.30 (Revised 2007) about Leases, which is assessed on the basis of capital market reactions. The results showedthat theapplication of PSAK No.30 (Revised 2007), about Leases, do nothave an influence onthe market. So we can saythe market does notsee thevalue relevance of PSAK No.30 (Revised 2007) about Leases.